Penyelesaian Sengketa Konstruksi melalui Negosiasi: Studi Kasus Perubahan AMDAL untuk Proyek Infrastruktur Ketenagalistrikan - Sebastian, Reza Rafly; Wisatrioda, Bayu; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
Electricity infrastructure development in Indonesia often faces disputes that can potentially hinder project completion. One of the prominent issues in construction disputes is the amendment to the EIA, which is legally regulated by Law Number 32 of 2009 and Government Regulation Number 22 of 2021. This study employs a qualitative approach with a case study on Project X, an electricity transmission line construction project. Data were collected through literature review, document analysis, and participatory observation of the negotiation process. The results show that the Contractor’s financial constraints were the root of the dispute in Project X, which had implications for the delayed completion of the amendment to the EIA. Negotiation, as an ADR mechanism, played a crucial role in resolving this dispute. The success of the negotiation was supported by interactional dynamics characterized by effective communication, adaptive leadership, and comprehensive data support. This case study affirms the repositioning of negotiation as an effective dispute resolution mechanism in the construction context, especially involving environmental aspects. This research also emphasizes the importance of compliance with EIA regulations, especially Law Number 32 of 2009 and Government Regulation Number 22 of 2021, and highlights the need for effective communication strategies in the negotiation process to reach a sustainable agreement.